2000
DOI: 10.1128/jcm.38.10.3800-3810.2000
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Phenotypic and Genotypic Methods for SubtypingCampylobacter jejuniIsolates from Humans, Poultry, and Cattle

Abstract: Six methods for subtyping of Campylobacter jejuni were compared and evaluated with a collection of 90 isolates from poultry, cattle, and sporadic human clinical cases as well as from a waterborne outbreak. The applied methods were Penner heat-stable serotyping; automated ribotyping (RiboPrinting); random amplified polymorphic DNA typing (RAPD); pulsed-field gel electrophoresis (PFGE); restriction fragment length polymorphisms of the flagellin gene, flaA(fla-RFLP); and denaturing gradient gel electrophoresis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(71 citation statements)
references
References 44 publications
5
65
0
1
Order By: Relevance
“…Harrington et al (1997) suggested that the fla-typing method cannot be considered as a stable method for the long-term monitoring of Campylobacter populations because the recombination within and between the flagellin loci of Campylobacter was demonstrated. On the other hand, it was suggested that the fla-typing method was a rapid and useful method in large-scale epidemiological studies (Nielsen et al 2000;Petersen and On 2000;Fitzgerald et al 2001a). It is necessary to exercise Total I II III IV IVa IVb1 IVb2 IVb3 IVc IVd V Campylobacter jejuni A 3, 0, 0 0, 0, 2 3, 0, 2 1, 0, 0 0, 1, 0 7, 1, 4 B 1, 0, 0 4, 5, 1 3, 0, 5 3, 0, 1 4, 2, 1 0, 1, 0 15, 8, 8 C 0, 0, 1 0, 0, 1 1, 0, 0 2, 0, 0 2, 0, 0 5, 0, 2 D 3, 1, 0 7, 0, 1 1, 0, 2 1, 0, 0 10, 3, 1 3, 1, 0 0, 3, 0 25, 8, 4 E 1, 0, 0 2, 0, 1 3, 0, 1 F 1, 0, 0* 1, 0, 0 2, 0, 0 G 1, 0, 1 0, 0, 1 2, 0, 0 3, 0, 2 I 1, 0, 0 1, 0, 0 J 4, 1, 1 1, 0, 0 0, 1, 0 5, 2, 1 K 1, 0, 0 0, 0, 1 1, 0, 1 L 2, 0, 1 2, 0, 0 1, 0, 0 5, 0, 1 O 7 , 0 , 0 0, 1, 0 7, 1, 0 R 8, 3, 0 1, 0, 0 0, 1, 0 9, 4, 0 S 1, 0, 0 1, 0, 0 U 0, 0, 1 0, 0, 1 Y 1, 0, 0 6, 0, 2 0, 0, 1 7, 0, 3 Z 2 1, 0, 0 1, 0, 0 Z 4 1, 0, 0 1, 0, 0 Z 5 0, 0, 1 0, 1, 0 0, 1, 1 Z 6 1, 0, 0 3, 1, 0 4, 1, 0 UT 1, 0, 0 3, 0, 1 3, 1, 2 2, 3, 3 7, 1, 3 2, 0, 1 4, 1, 0 1, 0, 0 1, 1, 0 0, 2, 0 24, 9, 10 Campylobacter coli 1, 0, 0 1, 0, 0 2, 0, 1 2, 1, 8 0, 0, 2 1, 0, 0 1, 0, 1 0, 2, 0 8, 3, 12…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harrington et al (1997) suggested that the fla-typing method cannot be considered as a stable method for the long-term monitoring of Campylobacter populations because the recombination within and between the flagellin loci of Campylobacter was demonstrated. On the other hand, it was suggested that the fla-typing method was a rapid and useful method in large-scale epidemiological studies (Nielsen et al 2000;Petersen and On 2000;Fitzgerald et al 2001a). It is necessary to exercise Total I II III IV IVa IVb1 IVb2 IVb3 IVc IVd V Campylobacter jejuni A 3, 0, 0 0, 0, 2 3, 0, 2 1, 0, 0 0, 1, 0 7, 1, 4 B 1, 0, 0 4, 5, 1 3, 0, 5 3, 0, 1 4, 2, 1 0, 1, 0 15, 8, 8 C 0, 0, 1 0, 0, 1 1, 0, 0 2, 0, 0 2, 0, 0 5, 0, 2 D 3, 1, 0 7, 0, 1 1, 0, 2 1, 0, 0 10, 3, 1 3, 1, 0 0, 3, 0 25, 8, 4 E 1, 0, 0 2, 0, 1 3, 0, 1 F 1, 0, 0* 1, 0, 0 2, 0, 0 G 1, 0, 1 0, 0, 1 2, 0, 0 3, 0, 2 I 1, 0, 0 1, 0, 0 J 4, 1, 1 1, 0, 0 0, 1, 0 5, 2, 1 K 1, 0, 0 0, 0, 1 1, 0, 1 L 2, 0, 1 2, 0, 0 1, 0, 0 5, 0, 1 O 7 , 0 , 0 0, 1, 0 7, 1, 0 R 8, 3, 0 1, 0, 0 0, 1, 0 9, 4, 0 S 1, 0, 0 1, 0, 0 U 0, 0, 1 0, 0, 1 Y 1, 0, 0 6, 0, 2 0, 0, 1 7, 0, 3 Z 2 1, 0, 0 1, 0, 0 Z 4 1, 0, 0 1, 0, 0 Z 5 0, 0, 1 0, 1, 0 0, 1, 1 Z 6 1, 0, 0 3, 1, 0 4, 1, 0 UT 1, 0, 0 3, 0, 1 3, 1, 2 2, 3, 3 7, 1, 3 2, 0, 1 4, 1, 0 1, 0, 0 1, 1, 0 0, 2, 0 24, 9, 10 Campylobacter coli 1, 0, 0 1, 0, 0 2, 0, 1 2, 1, 8 0, 0, 2 1, 0, 0 1, 0, 1 0, 2, 0 8, 3, 12…”
Section: Discussionmentioning
confidence: 99%
“…Molecular typing methods have been applied in order to discriminate between Campylobacter isolates of various origins (Nielsen et al 2000;Fitzgerald et al 2001a,b;Petersen et al 2001). Fla-typing appeared to be a suitable sub-typing method for Campylobacter jejuni and Campylobacter coli (Fitzgerald et al 2001b) and was a reliable epidemiological marker for Campylobacter isolates (Nielsen et al 2000). However, molecular epidemiological investigations with respect to antimicrobial resistant Campylobacter isolates are limited (Wu et al 2002;Lindmark et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Again, we do not have sufficient data to conclude that certain Campylobacter clones are host or niche specific. Studies looking at genotypes of Campylobacter from either animal or human sources did identify some strain types appearing to be associated only with humans, while other types are restricted to poultry (Koenraad et al 1995); however, most studies showed identical clones of Campylobacter could infect humans, poultry and cattle Hanninen et al 2000;Nielsen et al 2000;Fitzgerald et al 2001;Schouls et al 2003;Broman et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, because of low discriminatory powers of phenotypic methods (Wassenaar and Newell 2000), a plethora of genotypic methods such as flagellin gene-based polymerase chain reaction-restriction fragment length polymorphism (Ayling et al 1996;Mellmann et al 2004), fluorescent amplified fragment length polymorphisms (Duim et al 1999;Hopkins et al 2004), multilocus sequence typing (Dingle et al 2002;Sails et al 2003), pulsed-field gel electrophoresis (PFGE) (Chang and Taylor 1990;Ribot et al 2001), random amplification of polymorphic DNA (Madden et al 1996) and ribotyping (Qualicon, Wilmington, DE, USA) (Kiehlbauch et al 1994) have been developed for epidemiological typing of Campylobacter. Comparison and validation of these genotyping methods have been made in several studies (Patton et al 1991;Gibson et al 1995;Rautelin and Hanninen 1999;Nielsen et al 2000;Ono et al 2003), and no single typing method is yet considered as the golden standard for genotyping Campylobacter.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, these methods have only limited discriminatory power and various genetic methods have been developed for sub-typing purposes (Wassenaar and Newell 2000). Pulsed-field gel electrophoresis (PFGE) has been widely recognized as a sensitive method for molecular fingerprinting of Campylobacter isolates Nielsen et al 2000).…”
Section: Introductionmentioning
confidence: 99%